Transcatheter arterial embolization in the treatment of gastrointestinal ulcer bleeding - I. M. Musinov; A. E. Chikin; A. S. Ganin; E. Yu. Kachesov (Вестник хирургии имени И.И. Грекова)
The objective was to study the efficacy of transcatheter arterial embolization of gastric and duodenal vessels and to determine the indications for its use in gastroduodenal ulcer bleeding.Material and methods. The study was based on the results of arterial embolization in 61 patients with gastroduodenal ulcer bleeding.Results. Transcatheter arterial embolization of the left gastric artery, its branches and the gastroduodenal artery with an adhesive glue composite based on N-butyl-2-cyanoacrylate is highly effective in arresting bleeding permanently and preventing its relapse.Conclusion. Transcatheter arterial embolization is an alternative to the surgical treatment in patients with gastrointestinal bleeding.